Detection of Potential TNA and RNA Nucleoside Precursors in a Prebiotic Mixture by Pure Shift Diffusion‐Ordered NMR Spectroscopy. Issue 14 (1st February 2013) - Islam, Saidul; Aguilar, Juan A.; Powner, Matthew W.; Nilsson, Mathias; Morris, Gareth A.; Sutherland, John D.
Abstract In the context of prebiotic chemistry, one of the characteristics of mixed nitrogenous‐oxygenous chemistry is its propensity to give rise to highly complex reaction mixtures. There is therefore an urgent need to develop improved spectroscopic techniques if onerous chromatographic separations are to be avoided. One potential avenue is the combination of pure shift methodology, in which NMR spectra are measured with greatly improved resolution by suppressing multiplet structure, with diffusion‐ordered spectroscopy, in which NMR signals from different species are distinguished through their different rates of diffusion. Such a combination has the added advantage of working with intact mixtures, allowing analyses to be carried out without perturbing mixtures in which chemical entities are part of a network of reactions in equilibrium. As part of a systems chemistry approach towards investigating the self‐assembly of potentially prebiotic small molecules, we have analysed the complex mixture arising from mixing glycolaldehyde and cyanamide, in a first application of pure shift DOSY NMR to the characterisation of a partially unknown reaction composition. The work presented illustrates the potential of pure shift DOSY to be applied to chemistries that give rise to mixtures of compounds in which the NMR signal resolution is poor. The direct formation of potential RNA and TNA nucleoside precursors, amongst other adducts, was observed. These preliminary observations may have implications for the potentially prebiotic assembly chemistry of pyrimidine threonucleotides, and therefore of TNA, by using recently reported chemistries that yield the activated pyridimidine ribonucleotides.